Pengaruh Irigasi Defisit pada Fase Pengisian Polong terhadap Hasil dan Produktivitas Air Tanaman Kedelai (Glycine max [L] merr.) - Rismawan, Rendi; Rosadi, R.A. Bustomi; Zulkarnain, Iskandar (Jurnal Agricultural Biosystem Engineering, 2022)
Soybean is one of the main food commodities with a large amount of consumption. Most of the consumption comes from imports. Soybean production in Indonesia tends to decline. Efforts made are using superior varieties and expansion of planting areas. One of the superior soybean varieties is the Anjasmoro variety. Dry land has the potential for expansion of planting areas. But it is constrained by limited water supply. One way that can be done is by using irrigation deficits. This study aims to determine the effect of deficit irrigation on pod filling phase on yield and water productivity of soybean plants. This research was conducted at the Integrated Field Laboratory, Faculty of Agriculture, Lampung University in October 2018 until January 2019. This study used a Completely Randomized Design with five deficit irrigation treatment levels, namely P1 (100% KATT), P2 (80% KATT), P3 (60% KATT), P4 (40% KATT) and P5 (20% KATT) with four replications. The results showed that irrigation deficit treatment in the pod filling phase affected the yield and water productivity of soybean plants. Irrigation deficits on filling soybean pods cannot be applied. The provision of irrigation water must be given according to field capacity (100% KATT) for optimal yield and water productivity of plants with yields was 26.48 grams/pot and crop water productivity was 0.71 grams/L. Keywords: Anjasmoro, Deficit Irrigation, Pod Filling Phase, Soybeans.